2006
DOI: 10.1038/sj.bdj.4814042
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast carcinoma discovered in a dentigerous cyst — a case report

Abstract: This paper reports a patient with a history of breast cancer, who presented with altered sensation to the right lower lip and chin. An orthopantomogram showed a probable dentigerous cyst associated with an unerupted lower wisdom tooth, which was closely related to the inferior dental canal. The tooth and cyst were enucleated under general anaesthesia. The subsequent histopathology report concluded that the cyst contained metastatic adenocarcinoma from a primary breast tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Three breast carcinomas were discovered in a cyst located in the posterior mandible. The diagnosis was in three out of the four cases of a periapical cyst, and only in one case of a DC [ 48 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 A few cases of colorectal cancer metastasizing to the lips have been described, 26,27 and metastasis of breast adenocarcinoma to the lower lip has been observed. 28 The lip can also be a site for other metastatic cancers, including leiomyosarcomas, 10 cystosarcoma phyllodes of the breast, 29 and mesothelioma. 30 …”
Section: Key Pointsmentioning
confidence: 99%